ÇOCUKLARDA DUYGUSAL İSTİSMAR - ÖZTÜRK, SEMA (Fırat Üniveristesi, 2007)
Günümüzdeki teknolojik gelişmeler şaşırtıcı boyutlara ulaşmış olmaklabirlikte, bazı problemler ilkçağlardan günümüze intikal etmiş olup, bunlardanbazılarının bir problem olduğu dahi son zamanlarda kabul edilmiştir. Duygusalistismar da bunlardan biridir.Duygusal istismar en genel anlamıyla çocuk ve ergene duygularınırencide edecek biçimde davranılmasıdır. Çocuk ve ergenin bedenini ve kişiliğiniolumlu biçimde algılamasını, değerlendirmesini ve geliştirmesini engelleyici hertürlü olumsuz uyaranı kullanma, duygusal bakımdan kötü muamele yapmakdemektir.Bu çalışma ülkemizde henüz dikkat çeken bir konu olan duygusalistismar konusunun çeşitli yönleriyle araştırılması gerektiği inancıyla taramayöntemiyle inceleme yapılmıştır.Bu çalışmanın birinci bölümünde araştırmanın özellikleri ve tanımlarverilmiş, ikinci bölümünde çocuklarda duygusal istismarın anlamı, tarihçesi,kuramları açıklanmış, çocuk istismarı ve ihmali türleri araştırılmış, üçüncübölümünde araştırmanın yöntemi açıklanmış, dördüncü bölümünde duygusalistismarla ilgili yurt içi ve yurt dışında yapılmış olan araştırmalardan örneklerverilerek hukuki literatür taraması yapılmış, beşinci bölümünde ulaşılansonuçlar kısaca belirtilerek öneriler getirilmiştir.Bu çalışma ile eğitim, hukuk, psikoloji, tıp gibi birçok disiplin alanınıilgilendiren çocuk istismarının duygusal boyutu çeşitli yönleriyle incelenerek bukonuda başvurulabilecek bir kaynak oluşturması ümit edilmiştir.Yapılan araştırma ile, çocuklarda duygusal istismarın çok çeşitlivaryasyonlarda görülebildiği, bu davranışların istismar olduğu bilincinin henüzyerleşmediği, duygusal istismarın çocuğun kişilik gelişimi üzerinde olumsuzetkilere sebep olduğu ve bu istismar türünden korumaya ilişkin hükümlerin hemulusal hem uluslararası mevzuatta spesifik olarak yer almadığı tespit edilmiştir.Anahtar sözcükler: İstismar, çocuk, duygusal istismar, ebeveyn, okulöğretmen.

Although technological advancements reach to surprising diminutionssome problems remains identical, which were accepted as a problem recently?Emotional abuse is one of them.In most broad meaning, emotional abuse is the offending behaviour tothe feeling of the child or adolescent. The using whatever negative stimulantthat prevents perceive, appreciate and improve the body and personality of thechild and adolescent positively is bad treatment in point of the emotionalaspect.This study was done as research thoroughly method with a belief thatthe subject of emotional abuse which is a newly glaring matter in our countryshould be researched in various aspects.The subject of emotional abuse that is newly salient in our countryshould be investigated in terms of educationist and law of education.The characteristics of the research and descriptions were presented inthe first chapter of this study. The mean, the history and the theories of theemotional abuse in children were revealed and the types of the child abuse andneglect were researched in second chapter. The method is explanted in thirdchapter. The research about the emotional abuse, international documents andjudicial literature were searched in fourth chapter. The results and thesuggestions were discussed in fifth chapter.In this study, the emotional abuse in children was analysed in terms ofthe difference of the other abuse meaning content, examples, cause ofexistence, and location of national and international regulations. It is hopedthat, this study could be a theoretic reference that interested multidisciplineareas such as education law, psychology and medicine, examined manyaspects of emotional diminutions of child abuse.The emotional abuse in children can be seen in different variations, thiskind of behaviours can not be understood as an abuse generally, emotionalabuse give rise to negative effects on the development of the child, the rulesthat can protect from this abuse do not exist in both national and internationallegislations specifically were established with this research.Keywords: Abuse, child, emotional abuse, parent, school, teacher.
Emotional abuse of children
Keywords: Çocuk Sağlığı ve Hastalıkları